Efforts to Foster Students' Moral Literacy Thru the Use of Microlearning Videos in Eighth Grade Islamic Religious Education - Lisnawati Hayun; Herson Anwar; Firmansah Kobandaha; Iskandar; Ari Ariyanto (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the implementation of Islamic Religious Education learning using microlearning videos and to analyze the improvement of moral literacy among eighth-grade students at SMP Negeri 5 Satap Mootilango, Gorontalo Regency. The study employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 15 eighth-grade students. Data were collected through observation, interviews, documentation, and tests/student worksheets, and were analyzed using descriptive qualitative and simple quantitative techniques. The findings show that in Cycle I, the students’ average score was 66.4 with a mastery percentage of 33.33%. After improving the learning process in Cycle II by using more focused microlearning videos, more contextual examples, and more structured discussions, the average score increased to 83 with 100% mastery. The improvement of moral literacy was also reflected in students’ behavioral changes, including greater participation, better understanding of respect and obedience, greeting teachers, shaking hands respectfully, and speaking more politely. Therefore, microlearning videos proved to be an effective learning medium for fostering students’ moral literacy in Islamic Religious Education.